Optimization of linear taper design of a silicon-slab waveguide - Wildan Panji Tresna; Umar Ali Ahmad; Alexander William Setiawan Putra (Journal of Physics and Its Applications, 2021)
A linear taper is applied on a slab waveguide to control the divergence angle of the light. In this research, the slab waveguide design consists of silicon (Si) and SiO2 as the core and the substrate, respectively. The tapered design is optimized by measuring of Full-Width Half Maximum (FWHM) of the light after propagation in a Finite Different Time Domain (FDTD). The simulation results show that the optimized taper design is obtained when its length LT and width WL are 125 µm and 10 µm, respectively. This value is the optimal length to get the small diffraction angle of light during propagation in the waveguide. Thus, the divergence angle of the input light of the slab waveguide can be minimized by using this structure. One purpose of this research is to develop a miniaturized optical technology that is like the size of a chip.